2010
DOI: 10.2478/v10158-010-0019-8
|View full text |Cite
|
Sign up to set email alerts
|

Usage of Scanning Electron Microscopy for Particulate Matter Sources Identification

Abstract: Particulate matter (PM) diameter and shape are the most discussed physical properties considering behaviour characterisation, source identification, and possible effects on human health. Some groups of particles not only have a typical chemical composition but also a specific shape reflecting the method of their formation, so it is possible to deduce the source. A scanning electron microscope VEGA TS 5136 LSU (Tescan, s.r.o., Czech Republic) was used for PM imaging. PM air samples were captured on Millipore sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
1
7
0
4
Order By: Relevance
“…Abrasion of individual components of the mixtures must be confirmed by means of chemical analysis of the particulates collected on nitrocellulose filters and its subsequent comparison with the composition of each tested mixture. Thus, obtained results presented in this paper were compared with data published in scientific literature [10], [11] in which the same PM shapes were observed and assigned to specific source.…”
Section: Morphology Of Abraded Particulate Mattersupporting
confidence: 54%
See 2 more Smart Citations
“…Abrasion of individual components of the mixtures must be confirmed by means of chemical analysis of the particulates collected on nitrocellulose filters and its subsequent comparison with the composition of each tested mixture. Thus, obtained results presented in this paper were compared with data published in scientific literature [10], [11] in which the same PM shapes were observed and assigned to specific source.…”
Section: Morphology Of Abraded Particulate Mattersupporting
confidence: 54%
“…Particulate matter (PM) is considered a mixture of chemical components originated from a variety of sources with specific physical parameters (such as shape, diameter, electric charge, solubility, surface of the particles) and chemical composition (organic and inorganic compounds). Sources, mechanisms of formation, meteorological conditions, distance from the source and other conditions determine these basic parameters [10]. To gain a better understanding of PM origin and behaviour, it is necessary to describe their chemical composition and size distribution.…”
Section: Morphology Of Abraded Particulate Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…Characterization of PM 10 is of significant importance as it classifies the air pollutant into active and hazardous as well as non-active and unharmful particles. Many studies support the notion of PM characterization through SEM-EDS analysis and has reported different morphological shapes and chemical composition of PM, that cause severe lung diseases and illness ( Anake et al., 2016 ; Bahadar Zeb et al., 2018 ; Galvez et al., 2013 ; Genga et al., 2013 ; Grassi et al., 2004 ; Labrada-Delgado et al., 2012 ; Ličbinský et al., 2010 ; Ramirez-Leal et al., 2009 ; Ramirez-Leal et al., 2014 ; Tuvjargal et al., 2019 ). Then, we demonstrated the effectiveness of PM 10 exposure on A549 cells, by testing its inflammatory property within the cells, as it was previously reported that PM causes dysregulated inflammation in lungs to cause severe damage and toxicity ( Cevallos et al., 2017 ; de Barros Mendes Lopes et al., 2018 ; Horne et al., 2018 ).…”
Section: Discussionmentioning
confidence: 85%
“…Polycarbonate membrane filters were used for PM sampling (Willis et al, 2002). The particles trapped on the filters were covered with a 20-nm layer of gold for better monitoring of shape and size (Licbinsky et al, 2010;Weinbruch & Ebert, 2004). PM imaging was performed in the laboratory of the Transport Research Centre in Brno, Czech Republic.…”
Section: Pm Morphologymentioning
confidence: 99%